2021
DOI: 10.1039/d0bm01333a
|View full text |Cite
|
Sign up to set email alerts
|

A simple self-adjuvanting biomimetic nanovaccine self-assembled with the conjugate of phospholipids and nucleotides can induce a strong cancer immunotherapeutic effect

Abstract: Biomimetic nanoparticles have potential applications in many fields for their favorable properties. Here, we developed a self-adjuvanting biomimetic anti-tumor nanovaccine, which was self-assembled with an amphiphilic conjugate synthetized with phospholipids...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The fluorescence intensity in the MCO NVs group was 2.8- and 2.0-fold higher than those of the Free OVA and the Free MPLA/CpG ODN/OVA (Free MCO) group, respectively (Figure S5). These results indicated that MCO NVs could significantly improve the BMDCs’ uptake of antigens and adjuvants, with the mechanism mainly owing to the formation of the hollow spherical nucleic acid (SNA) nanostructure which has a great cellular entry ability. …”
Section: Resultsmentioning
confidence: 85%
“…The fluorescence intensity in the MCO NVs group was 2.8- and 2.0-fold higher than those of the Free OVA and the Free MPLA/CpG ODN/OVA (Free MCO) group, respectively (Figure S5). These results indicated that MCO NVs could significantly improve the BMDCs’ uptake of antigens and adjuvants, with the mechanism mainly owing to the formation of the hollow spherical nucleic acid (SNA) nanostructure which has a great cellular entry ability. …”
Section: Resultsmentioning
confidence: 85%
“…To further explore the pathway of R837@HM-NPs into BMDCs, we pretreated these cells with several cellular uptake inhibitors and blocked the corresponding endocytic pathway. 26 , 27 BMDCs were treated with filipin (15 μg/mL), amiloride (10 μg/mL), chlorpromazine (10 μg/mL), monensin (10 μg/mL), methyl-β-cyclodextrin (10 μg/mL), and ethylisopropylamiloride (20 μg/mL) at 37 °C for 2 h. The pretreated cells then were co-incubated with R837@HM-NPs for 4 h and untreated cells were used as a negative control. The cells were then trypsinized, centrifuged, and lysed by ultrasonication.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained nanovaccines could provide sustained and effective antigen stimulation, promote the release of some immune factors, further boost significantly anti-tumor immunity to inhibit tumor growth. 86 Moreover, there is another way to introduce CpG into tumor nanovaccines through the formation of covalent bonds between S and other atoms. For example, Zhu et al developed albumin/albumin-binding vaccines (AlbiVax) nanocomplexes that achieved high efficiency co-delivery of antigen and adjuvant CpG.…”
Section: Cpg Loaded In Nanovaccines By Covalent Bondingmentioning
confidence: 99%